Efektivitas Bimbingan Perkawinan Pra-Nikah untuk Mencapai Keluarga Sakinah di Kecamatan Silangkitang - Muhammd Arif Siregar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Marriage is a contract that legitimizes the relationship and outlines the rights and obligations between a man and a woman. To prepare for marriage, the Ministry of Religion provides premarital guidance through the local KUA, including in Silangkitang District. This guidance aims to help couples build a sakinah, mawaddah, and warahmah family. This study examines the effectiveness of premarital guidance at KUA Silangkitang from the perspectives of both the institution and prospective brides and grooms. Using a qualitative field research approach, data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s theory. Results show that premarital guidance is effective according to the KUA in five aspects, and effective according to prospective couples in four aspects. However, cultural factors remain less effective due to a lack of understanding among some participants.